Rethinking gold(II) porphyrins: an inherent wave distortion - Ghosh, Abhik; Conradie, Jeanet (Comptes Rendus. Chimie)
Relativistic DFT (OLYP-D3/ZORA-STO-TZ2P) calculations predict low adiabatic ionization potentials for gold(II) porphyrins, from 4.60 eV for Au[TPP] (TPP $=$ tetraphenylporphyrin) to 5.34 eV for Au[TPFPP] [TPFPP $=$ tetrakis(pentafluorophenyl)porphyrin]. These values are over 1 eV lower than those calculated for analogous silver(II) porphyrins, reflecting much greater relativistic destabilization of the Au 5d orbitals relative to Ag 4d orbitals. Interestingly, our calculations also place the observed structural distortion of Au[TPP] in an entirely new light. The electronic imperative of the Au(II) center to assume a pseudo-d10 configuration drives a wave deformation of the porphyrin core that allows for Au(d$_{x^{2}-y^{2}}$)–porphyrin(${π }$) mixing. The lateral compression–elongation of the porphyrin (unequal pairs of Au–N bonds), in contrast, appears to be a secondary effect, a consequence of the wave deformation. The wave distortion results in significant ${π }$ spin populations on the porphyrin macrocycle, leaving behind only about 20–25% of the spin density on the gold. The effect is specific to gold: silver(II) porphyrins exhibit strictly planar cores with approximate $D_{4h}$ local symmetry at the metal.